Effect of antenatal education in improving maternal confidence and reducing anxiety about labor in Primigravida women attending Saveetha medical College and hospital, Chennai, Tamilnadu, India - HEMA SWAROOPA.N,; G. DEEPTHI, (International Journal of Pharma and Bio Sciences, 2017)
Child birth is perceived as a natural process in woman’s life. The women those who attend delivery for the first time definitely would have some sort of fear and anxiety. This fear is due to lack of knowledge and idea about what is happening around her and it will lead to lack of cooperation during delivery. Antenatal education gives knowledge about labour and teach how to overcome pain and what to do during each stage of labour. This may reduce the anxiety associated with child birth. This study was conducted to find out whether the antenatal education is effective in reducing maternal anxiety about labor in primigravida women attending Saveetha medical college and Hospital, which is located in rural community where the women are more exposed to myths. Twenty subjects were taken from obstetric ward and they were equally divided into two groups. The pre-test and post-test evaluation of maternal anxiety was made with the childbirth attitude questionnaire. Subjects were treated for their complaints and the antenatal education with different syllabus were given to both the groups individually. The post-test values were noted. The data was statistically analyzed using paired t-test and student t-test. The pre-test mean value of Group A and Group B is 38.8 and 40.1 respectively. The post-test mean value of Group A is 36.4 and in Group B is 23.6. This study showed the statistically significant reduction in maternal anxiety about labor in primigravida women who attended antenatal classes (p=0.0016). This study concludes that antenatal education helps in reducing maternal anxiety about labor in primigravida mothers.